UNDERSTANDING THE PRACTICES THAT DEFINE PENTECOSTAL CHRISTIANITY IN NIGERIA - Amadi, Fred A. (European Scientific Journal, ESJ, 2013)
In parts of Central and Southern Nigeria, there are Pentecostal Churches everywhere. Many of the pastors in charge of the churches are often implicated in different acts of wrongdoing. Despite this, the churches are often packed with worshippers. Ordinarily, pastors’ wrongdoing ought to minimize the devotion adherents bestow on their pastors. But in the Nigerian context, the involvement of pastors in wrongdoing tends to draw more adherents. This is a puzzle that this paper examines. Three objectives, including the examination of what draws Nigerians to Pentecostal Christianity, were examined. Documents from diverse sources were accessed as data. The documents were displayed in text boxes and interpreted. To avoid high-inference interpretation, comments were elicited from research participants. Key themes of Nigerian Pentecostal Christianity’s message are found to focus on prosperity, miraculous healing, and neutralization of witchcraft. These themes resonate with indigenous religious world-view. In the African religious world view, unemployment, poverty, diseases, accidents, untimely death and so on cannot afflict victims if not through the human agents that work with the demons. Nigeria’s Pentecostal pastors tap into this myth to construct anxiety-reducing sermons. The sermons promise adherents freedom from unemployment, poverty, accidents and diseases. Aspects of the data that see Pentecostal sermons as mere puffery necessitate a recommendation that urges Pentecostal pastors to put their message beyond demagogy by explaining in practical terms, how to attain the amazing hopes their message hold out.